First Offensive Shot in Elite Table Tennis - Michael Fuchs; Martin Lames (Universidad de Granada, 2021)
At the (very) first shots in table tennis, players face a basic tactical decision: either return the ball short and passively or attack it with an offensive shot. In the first case, there is lower risk but no pressure for making the point, in the second case pressure is created, but at the cost of high risk, because the serve and other prior "passive" shots try to make an offensive shot as difficult as possible, typically being short and flat. Thus, the real turntable of a rally is this shot - in this study called "first offensive shot" (FOS) - which is the transition from passive to offensive play. This study investigates the FOS, which is defined as the first shot after the serve without any kind of backspin/side-backspin, for 90 matches (nrally = 7449) of the 2016 Rio Olympic Games. The FOS parameters - laterality, technique and position to the table at the point of contact - and the respective winning probabilities are analysed. The influences of sex and the players' ranking (resulting in three different match categories) on those parameters are studied. Descriptive statistics about the incidences of the FOSs show that four typical FOSs cover 98% of all FOSs. Chi-square tests reveal a significant relation between sex and these typical FOSs. Regarding the match categories, the tests prove a significant relation between match categories and FOS tactics for both genders. A difference in the FOS tactics between the serving and the receiving player is found as well. The winning probabilities show that using topspin (FH and BH) as FOS was an advantage in every match category, whereas using flip as FOS led mostly to a winning probability below 50% for the FOS player. Except for the FH flip in women's matches, it was always a bigger advantage for the FOS player if he/she could finish the rally at latest with the follow up attack after the FOS which means that the winning probability for the FOS player decreased in the longer rallies. Compared to prevailing methods in table tennis match analysis, which are based on fixed shot numbers, taking the FOS as object of analyses of rally opening is an innovative new approach focusing on the tactical meaning of shots that is not expressed in shot number.